Virological and immunological correlates of mother-to-child transmission of cytomegalovirus in The Gambia. - Kaye, S; Miles, D; Antoine, P; Burny, W; Ojuola, B; Kaye, P; Rowland-Jones, S; Whittle, H; van der Sande, M; Marchant, A (2008)
BACKGROUND: Cytomegalovirus (CMV) is the most common congenital infection and can follow primary and recurrent maternal infection. We studied correlates of vertical transmission of CMV in The Gambia, where most children acquire CMV during the first year of life. METHODS: A cohort of 281 mothers and infants was recruited at birth. Infants were prospectively followed up for CMV infection during the first year of life. Excretion of CMV and antiviral immune response were studied at birth in mothers of children infected in utero, early during infancy, or late during infancy or not infected at 1 year of age. RESULTS: Congenital infection was diagnosed in 3.9% of newborns, and 85% of children were infected by 1 year. Excretion of CMV in colostrum or in the genital tract was more common in mothers of congenitally (100%) or early infected children (48%) than in mothers of late-infected (20%) or uninfected children (27%). Higher rates of viral excretion were associated with significantly higher levels of serum anti-CMV immunoglobulin G and higher frequencies of CMV-specific CD4+ T cells. CONCLUSION: In the context of recurrent maternal infection, transmission of CMV in utero and during early postnatal life is associated with excretion of the virus in colostrum and the genital tract.